Non-linear Dynamics Characterization from Wavelet Packet Transform for Automatic Recognition of Emotional Speech (2016)
ABSTRACT: We propose a new set of features based on non-linear dynamics measures obtained from the wavelet packet transform for the automatic recognition of “fear-type” emotions in speech. The experiments are carried out using three different databases with a Gaussian Mixture Model for classification. The results indicate that the proposed approach is promising for modeling “fear-type” emotions in speech.